Zwitterionic Sulfonates as m/z Shift Reagents for 5-Methylcytosine Detection in Deoxyribonucleic Acids (DNA) Using Flow Injection Analysis and Electrospray Ionisation Mass spectrometry. Issue 4 (August 2015) - Podjava, Anton; Kistkin, Svjatoslav; Ausekle, Elina; Mekss, Peteris; Zicmanis, Andris
5-Methylcytosine (5-MC) is an important epigenetic modification of DNA. Abnormally high concentrations of this substance appear because of the hypermethylation of cytosine. Therefore, the measurement of the quantity of this compound in mammals is of great importance. Recently, we reported that several imidazolium-based zwitterionic sulfonates form complexes with 5-MC in solution, which can be studied by electrospray ionisation mass spectrometry (ESI-MS). It is shown in this paper that such an association can be utilised for the detection of 5-MC in a DNA sample using high-throughput a flow injection analysis ESI-MS method. A variety of the sulfonate zwitterions have been tested as m / z shift reagents to increase the selectivity of the analysis. It is shown that either of the zwitterions can be used without the loss of sensitivity. The performance of the method was tested in terms of linearity range, sensitivity, intra- and between-day precision and accuracy, matrix effect and carryover. The method described is characterised by simplicity, a good limit of quantitation (1 pg injected) and low run times (at least 50 injections per hour). In addition, high-performance liquid chromatography and tandem mass spectrometry are not required. The possibility exists to widen the scope of the method to other amidine-containing compounds present in more complicated matrices.